Kesehatan Mental dan Strategi Koping Mahasiswa Keperawatan pada Masa Pandemi COVID-19 - Rian Maulana Yusup; Lisa Musharyanti (Journal of Telenursing (JOTING), 2021)
This study aims to assess stress levels, mental health, depression and anxiety in nursing students during the COVID-19 pandemic. The method used in this study is a literature study on the PubMed, ScienceDirect, Scilit, Proquest and Google Scholar databases. The results show that the COVID-19 disease outbreak has become a threat to global health. Its spread which continues to this day, greatly affects the education sector. Students carry out coping strategies to avoid factors that can reduce their mental health conditions. In conclusion, students have a higher stress level than female students. However, in general, the respondents had normal levels of depression, normal levels of anxiety, normal stress levels and did not have clinically significant insomnia. Keywords: COVID-19, Mental Health, Nursing Students, Coping Strategies, Literature Study